PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI (Studi kasus pada Badan Pengembangan Sumber Daya Manusia Daerah Provinsi Jawa Tengah) - Rizka Putri Hoirunisa, 13.05.51.0033 (Students Journal of Economic and Management, 2017)
The purpose of this study determined the effect of leadership, work environment, and motivation to employee performance BPSDMD Central Java Province. This study also aims to determined jointly the effect of three independent variables on the dependent variable and to determined which variable most dominant influence among the three independent variables on the dependent variable. This research used a qualitative research, population of employees was 203 employees. This sample studywas 67 randomizedemployees and collection data used questionnaire with Likert scale. Based on the calculation resulted SPSS 24 of the t test on theleadership variable acquired a significance of 0.379> 0.5, Ho is accepted and Ha = H1 rejected, working environment variable obtained a significance of 0.000 0.50, Ha = H3 Ho rejected and accepted. F test results showed a significant value of 0.000